Comparison of Organ and Effective Photon Dose Coefficients for Reference Phantoms in Articulated and Upright Postures in Cranial and Caudal Irradiation Geometries. Issue 5 (May 2019) - Bales, Kathryn; Dewji, Shaheen
Abstract : Abstract: Traditionally, dose estimations have been performed predominantly using anthropomorphic phantoms in an upright posture. However, an exclusively upright posture could reduce accuracy when estimating organ absorbed and effective doses for exposures in realistic postures. In this work, effective dose coefficients were computed using International Commission on Radiological Protection Publication 103 recommendations for monoenergetic photon plane sources (0.05–20 MeV) directed upward from below the feet (caudal) and downward from above the head (cranial) for articulated adult male and female stylized phantoms. The Monte Carlo radiation transport code and the Phantom With Moving Arms and Legs were used to calculate organ absorbed dose and effective dose coefficients for upright and two bent (45° and 90°) phantom postures. The resulting coefficients for the bent phantoms were compared to those for the upright phantoms to determine whether the upright phantoms provide a comparable and conservative estimate when conducting dose estimations/reconstructions. For the caudal source, most organs received higher doses when in a bent posture. For the cranial source, the breast, brain, and eyes received lower doses in the bent compared to the upright posture, while all other organs received higher doses. The effective doses for the articulated phantoms were higher than for the upright posture for both irradiation geometries, which could have implications when using the traditional model to estimate or reconstruct radiation doses during actual exposures. Abstract : Supplemental digital content is available in the text.